Membangun Kesiapsiagaan Bencana pada Siswa Melalui BLU-DISCARE sebagai Inovasi Pendidikan Kebencanaan di Sekolah Guna Mewujudkan Generasi Tangguh Bencana - Hayatul Khairul Rahmat; H Hasrian; M. Aji Bimantara (Jagratara: Journal of Disaster Research, 2023)
This research aims: (1) to provide an understanding of the development of disaster preparedness to students through disaster education in order to create a disaster resilient generation; (2) to be able to explain the concept of BLU-DISCARE (Budi Luhur Disaster Care) as a disaster education innovation in creating a disaster resilient generation; and to explain the implementation of BLU-DISCARE (Budi Luhur Disaster Care) as a disaster education innovation in creating a disaster resilient generation. This research uses qualitative methods with data collection techniques using literature study and observation. The findings from this research are: (1) building disaster preparedness (disaster awareness) among students in schools through disaster education aims to maintain human values and attitudes towards disaster risk, understanding related to disaster risk, knowledge and skills for disaster prevention; (2) BLU-DISCARE (Budi Luhur Disaster Care) as a disaster education innovation has a work flow starting from risk mapping, then organizing, educating, and ending with advocacy; and (3) implementation of BLU-DISCARE (Budi Luhur Disaster Care) as a disaster education innovation in the form of activities such as counseling about the risk of earthquake disasters, training in making disaster literacy media, counseling on disaster mitigation in schools using the kamishibai method, disaster evacuation simulations, and simulations. search and rescue in disaster conditions.